Aprender e ensinar a ser gaúcho dentro do Grupo de Danças Biriva Tropeiros de Dois Mundos - Borba, Daniela Farias Garcia de (2013)
This dissertation is part of the Master Degree research of the Post-Graduation Program in Education of Federal University of Santa Maria/ RS, bound into the Education and Arts line and into the Research Group Difference, Education and Culture (DEC-UFSM). The investigation, of ethnographic perspective, has as object the study the dancing group Agrupando Biriva Tropeiro de Dois Mundos , from Encantado city / RS, and it searches for evidence in the meanings of the dance for the participants of this group, in order to take it as more one culture once it generates an own universe of meanings, it produces identities and it deals ways of teaching and learning to be gaúcho. This Master Degree essay is a possible version of comprehension of the process of learning and production of meanings about the gaúcha traditionalist culture inside biriva dancing group. It enrolls as an ethnographic, a narrative text, in which there is the intention of the author‟s impressions, ways and misleading let their footprints for the reader knows the insertion and comprehension process of reality in that this research is submerged, as in the reality of the researched field as the theoretical reality and the author‟s subjectivity.